ONTOGENESIS AND AGE STRUCTURE OF ADONIS VERNALIS L. POPULATIONS IN THE CONDITIONS OF NORTHERN KAZAKHSTAN - Sultangazina, G.J.; Kuprijanov А.N.; Kuprijanov О.А.; Beyshov, R.S. (Scientific Journal of Pedagogy and Economics, 2020)
The current article presents study results made on the coenoflora of Adonis vernalis L. in Northern Kazakhstan. The materials have been gathered in the course of field research taking into account the literary data. Ontogenesis and age structure of the coenopopulations are provided on the basis of detailed-route studies. The study of age-related stages was carried out on the territory of Northern Kazakhstan (Akmola and North Kazakhstan regions) in 2018-2019. A. vernalis is a short-stem grassy polycarpic plant, it is represented in Northern Kazakhstan by the populations of dry meadows (Kokshetau Upland) and real meadows (the forest-steppe of North Kazakhstan region). Ontogenesis of A. vernalis has three periods and 7 age stages. Plants have low seed productivity. Seeds have a long endogenous peace related to the underdevelopment of a seed germ. A characteristic feature is the presence of a long pregenerative period in plants of the "steppe" type coenopopulations and its reduction in the "meadow" type coenopopulations. There have been studied thirteen coenopopulations of A. vernalis located in Akmola and North Kazakhstan regions. Coenopopulations of A. vernalis are bound to four main habitats: forest edges, meadow steppes, meadows, artificial plantations. By age, young populations are formed on forest edges, and according to the "delta - omega" classification, there are mature coenopopulations. Mature coenopopulations are mostly formed in meadow steppes, but according to the "delta - omega" classification, all coenopopulations are aging. On meadows, there are many young coenopopulations, but according to the "delta - omega" classification, they are all mature. In artificial plantings, the majority of coenopopulations are aging, but according to the "delta - omega" classification, they are all mature. Thus, changes in habitual living conditions lead to the aging of A. vernalis coenopopulations. By density (pcs/100 m2) all populations are divided into three groups: high, medium, low. All forest edge coenopopulations have a high density, in meadow steppes, the density is average, on meadows and in artificial plantings it is low. The recovery index in most coenopopulations is less than one which indicates a low recovery in A. vernalis populations. The range of age stages shows that in most coenopopulations they are normal, the exception is CP-5 (among artificial plantings) which indicates an old stage of the population and possibly its soon elimination.